Mitigation potential and environmental impact of centralized versus distributed BECCS with domestic biomass production in Great Britain. Issue 10 (7th July 2019) - Albanito, Fabrizio; Hastings, Astley; Fitton, Nuala; Richards, Mark; Martin, Mike; Mac Dowell, Niall; Bell, Dave; Taylor, Simon C.; Butnar, Isabela; Li, Pei‐Hao; Slade, Raphael; Smith, Pete
Abstract: New contingency policy plans are expected to be published by the United Kingdom government to set out urgent actions, such as carbon capture and storage, greenhouse gas removal and the use of sustainable bioenergy to meet the greenhouse gas reduction targets of the 4th and 5th Carbon Budgets. In this study, we identify two plausible bioenergy production pathways for bioenergy with carbon capture and storage (BECCS) based on centralized and distributed energy systems to show what BECCS could look like if deployed by 2050 in Great Britain. The extent of agricultural land available to sustainably produce biomass feedstock in the centralized and distributed energy systems is about 0.39 and 0.5 Mha, providing approximately 5.7 and 7.3 MtDM /year of biomass respectively. If this land‐use change occurred, bioenergy crops would contribute to reduced agricultural soil GHG emission by 9 and 11 Mt CO 2 eq /year in the centralized and distributed energy systems respectively. In addition, bioenergy crops can contribute to reduce agricultural soil ammonia emissions and water pollution from soil nitrate leaching, and to increase soil organic carbon stocks. The technical mitigation potentials from BECCS lead to projected CO2 reductions of approximately 18 and 23 Mt CO 2 /year from the centralized and distributed energy systems respectively. This suggests that the domestic supply of sustainable biomass would not allow the emission reduction target of 50 Mt CO 2 /year from BECCS to be met. To meet that target, it would be necessary to produce solid biomass from forest systems on 0.59 or 0.49 Mha, or alternatively to import 8 or 6.6 MtDM /year of biomass for the centralized and distributed energy system respectively. The spatially explicit results of this study can serve to identify the regional differences in the potential capture of CO2 from BECCS, providing the basis for the development of onshore CO2 transport infrastructures. Abstract : This study identifies two plausible bioenergy production pathways for bioenergy with carbon capture and storage (BECCS) based on centralized and distributed energy systems to show what BECCS could look like if deployed by 2050 in Great Britain. The technical mitigation potentials from BECCS lead to projected CO2 reductions of approximately 18 and 23 Mt CO 2 /year from the centralized and distributed energy systems respectively. To meet the emission reduction target of 50 Mt CO 2 /year from BECCS, it will be necessary to produce solid biomass on 0.59 or 0.49 Mha, or alternatively to import 8 or 6.6 MtDM/year of biomass.